Juridical Analysis of Constitutional Court Decisions Regarding Tax Collection against Taxpayers Who Are Declared Bankrupt: Case Study of Constitutional Court Decision Number 41/PUU-XVIII/2020 - Mochamad Amaludin; Ratih Lestarini; Tjip Ismail (Budapest International Research and Critics University, 2022)
This study aims to analyze the implications of the Constitutional Court's decision on state rights in the context of tax collection, tax law enforcement efforts and fair legal protection and certainty for all parties interacting with legal entities. This study indicates that the state's right to collect taxes is a valid authority not only because it is lawful utilizing normative legal research and a legal approach as normative juridical research that directs research on secondary material such as books, positive legislation, and written norms. Article 23A of the 1945 United States Constitution states that it is constitutionally anchored on the Constitution. This analysis also demonstrates that the arrangements outlined in Article 2 paragraph 6 and Article 32 paragraph 2 of the KUP Law, which are subject to material review, are extremely important and helpful for preserving legal certainty and justice in tax payments.